1997
DOI: 10.1007/pl00004955
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine inhibits catalepsy induced by olanzapine and loxapine, but prolongs catalepsy induced by SCH 23390 in rats

Abstract: Loxapine (0.3 mg/kg s.c.), olanzapine (10 mg/kg s.c.) and SCH 23390 (R-(+)-chloro-2, 3, 4, 5-tetrahydro-3-methyl-5-phenyl-1-H-3-benzazepine; 1 mg/kg, s.c.), but not clozapine (10 mg/kg, s.c.), induced catalepsy in rats. Co-administration of clozapine (1, 3 and 10 mg/kg s.c.) dose-dependently inhibited loxapine-induced catalepsy. Clozapine (10 mg/kg s.c.) also prevented the induction of catalepsy by olanzapine. In addition, clozapine abolished the catalepsy induced by loxapine when it was administered after the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 18 publications
4
11
0
Order By: Relevance
“…1) in agreement with previous studies (Antonelli et al, 1991;Wellman and Davies, 1992;Mathe et al, 1996). In contrast, the ␣2-AR antagonist idazoxan increased the spontaneous activity of both intact and lesioned rats (i.e., displaying an antiparkinsonian activity), in keeping with previous reports showing that several ␣2-AR antagonists increase motor activity under normal conditions and improve motor functions in experimental and human parkinsonism (Kalkman et al, 1997;Bezard et al, 1999;Villegier et al, 2003).…”
Section: Effects Of Noradrenergic Agents On Locomotor Activitysupporting
confidence: 91%
“…1) in agreement with previous studies (Antonelli et al, 1991;Wellman and Davies, 1992;Mathe et al, 1996). In contrast, the ␣2-AR antagonist idazoxan increased the spontaneous activity of both intact and lesioned rats (i.e., displaying an antiparkinsonian activity), in keeping with previous reports showing that several ␣2-AR antagonists increase motor activity under normal conditions and improve motor functions in experimental and human parkinsonism (Kalkman et al, 1997;Bezard et al, 1999;Villegier et al, 2003).…”
Section: Effects Of Noradrenergic Agents On Locomotor Activitysupporting
confidence: 91%
“…This separation of antipsychotic drugs into 'loose' and 'tight' binding to D2, relative to that for dopamine, is consistent with the findings by Kalkman et al 71 These authors were able to reverse catalepsy induced by olanzapine and loxapine (both more loosely bound than dopamine), but were not able to reverse that by Figure 3 The therapeutic concentrations of various antipsychotic drugs consistently occupy 75-76% of dopamine D2 receptors (data from Figure 2), but similar calculations for the dopamine D3 and dopamine D4 receptors did not reveal any constant percent occupancy for all the antipsychotic drugs. CPZ, chlorpromazine; Cloz., clozapine; Halo., haloperidol; Molin., molindone; Olan., olanzapine; Raclo., raclopride; Remox., remoxipride; Sulp., S-Sulpiride; Thior., thioridazine; Flupen., cis-flupentixol; per., perphenazine.…”
Section: Antipsychotic Drugs Which Bind More Loosely Than Dopamine Tosupporting
confidence: 92%
“…Preclinical behavioural studies have demonstrated that loxapine may induce catalepsy in rats to the same extent as olanzapine, and these effects may be abolished by clozapine administration, but only when it is administered after the catalepsy is fully developed [33]. In discriminative stimulus comparisons, loxapine may only induce minimal generalization, similarly to haloperidol, whereas clozapine has been demonstrated to induce full dose-related generalization in the absence of response suppression [34].…”
Section: Overview Of Inhaled Loxapinementioning
confidence: 99%